2003
DOI: 10.4049/jimmunol.171.4.1707
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of T Cell Activation Via CD147 Through Novel Modulation of Lipid Rafts

Abstract: The plasma membrane is compartmentalized into microdomains and the association/dissociation of receptors and signaling molecules with/from these membrane domains is a major principle for regulation of signal transduction. By following the reorganization of microdomains on living cells and performing biochemical studies, we show that Ab targeting of the T cell activation-associated Ag CD147 prevents TCR stimulation-dependent reorganization and clustering of microdomains. Triggering CD147 induces a displacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 55 publications
5
65
0
Order By: Relevance
“…Finally, exposure to minocycline or anti-EMMPRIN Abs reduced the surface levels of the T cell activation marker, CD25, as well as reduced levels of IFN-g and IL-10 from PBMCs (Fig. 4) (5). These similarities support the contention that minocycline may act, in part, through suppressing EMMPRIN-mediated pathways.…”
Section: Discussionsupporting
confidence: 67%
“…Finally, exposure to minocycline or anti-EMMPRIN Abs reduced the surface levels of the T cell activation marker, CD25, as well as reduced levels of IFN-g and IL-10 from PBMCs (Fig. 4) (5). These similarities support the contention that minocycline may act, in part, through suppressing EMMPRIN-mediated pathways.…”
Section: Discussionsupporting
confidence: 67%
“…6A and 6B, CD147 silencing did not affect plasma membrane-expressed PMCA4 (SA pull-down). In addition to its shuttling function to the plasma membrane, we showed previously that CD147 influenced the lipid raft localization of CD48 and CD59 (14). However, density gradient centrifugation with CD147-silenced cells, stimulated or not with OKT3 plus Leu-28, showed that silencing of CD147 did not change the distribution of PMCA4 from the nonraft to the lipid raft compartment (Fig.…”
Section: Na(+)/k(+) Atpasementioning
confidence: 85%
“…Furthermore, CD147 was shown to influence T cell proliferation (10)(11)(12), thymocyte maturation (13), NFAT transcriptional activity, and IL-2 production (14,15). Recently, CD147 levels were described as a surrogate marker of activated regulatory T cells (16,17), and Abs specific to the extracellular domain of CD147 showed potent immunomodulatory capacities (11,18).…”
mentioning
confidence: 99%
“…Recently, increased expression of CD147 was observed on CD3+ T cells from systemic lupus erythematosus patients compared to healthy donor T cells, likely indicating their increased activation (Pistol et al 2007). Engagement of CD147 with the MEM-M6/6 anti-CD147 monoclonal antibody was found to inhibit anti-CD3 induced T cell activation (Koch et al 1999), presumably by inhibiting the reorganization and clustering of GPI-anchored coreceptors within lipid rafts which in turn alters down-stream signaling events (Staffler et al 2003). For T cells, the level of CD147 expression also correlates with the state of differentiation, whereby immature thymocytes express higher CD147 levels than do mature resting T cells (Kirsch et al 1997).…”
Section: Role In Lymphocyte Migration and Activationmentioning
confidence: 99%